Degenerate and non-degenerate all-optical switches using violet phosphorus nanosheets. Issue 13 (9th March 2023) - Gao, Yang; Hu, Yueqiu; Ling, Cheng; Rui, Guanghao; He, Jun; Gu, Bing
Abstract : In this work, SSPM effects of VP Ns and their reaction dynamics were studied for the first time (left). Using the superior coherence electronic nonlinearity of VP Ns, all-optical switches based on the SSPM effect (right) were prepared. Abstract : As an allotrope of phosphorus, layered violet phosphorus (VP) has a wide range of applications in electronics, photonics, and optoelectronics. However, its nonlinear optical properties remain to be explored. In this work, we prepare and characterize VP nanosheets (VP Ns), investigate their spatial self-phase modulation (SSPM) effects, and develop them in all-optical switching applications. The ring forming time of SSPM and the third-order nonlinear susceptibility of monolayer VP Ns were found to be about 0.4 s and 10 −9 esu, respectively. The mechanism of SSPM formed by coherent light–VP Ns interaction is analyzed. Using the superior coherence electronic nonlinearity of VP Ns, we realize degenerate and non-degenerate all-optical switches based on the SSPM effect. It is demonstrated that the performance of all-optical switching can be controlled by adjusting the intensity of the control beam and/or the wavelength of the signal beam. The results will help us to better design and realize non-degenerate nonlinear photonic devices based on two-dimensional nanomaterials.